Do Virtual Race Events Improve Physical Activity Behavior? - Rizky Suganda Prawiradilaga; Fajar Awalia Yulianto; Umar Islami; Mirasari Putri (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Physical inactivity remains a major global health concern, with approximately one in four adults not meeting recommended activity levels. Virtual competitions have emerged as an alternative approach to encourage physical activity, especially following the COVID-19 pandemic. This study aimed to evaluate the impact of a virtual race event on physical activity behavior in adults with a sedentary lifestyle. A cohort study was conducted involving 68 participants, of whom 32 completed both pre- and post-event assessments. Physical activity levels were measured using the Global Physical Activity Questionnaire (GPAQ) before and four weeks after the virtual race. Participants were categorized into a sedentary group (<600 MET-minutes/week) and an active group (≥600 MET-minutes/week) based on baseline data. The McNemar test was used to assess changes in physical activity classification. Results showed that in the sedentary group, the number of active participants increased from 0 to 5 (41.67%), while in the active group, the number of participants who remained active decreased from 20 to 13 (65%). However, the difference between the groups was not statistically significant (p = 0.56). These findings suggest that while virtual race events may offer motivational value, their short-term effect on physical activity behavior may be limited without additional support mechanisms. Future studies should consider larger samples, longer follow-up periods, and the integration of behavioral strategies to enhance engagement and promote sustained physical activity, especially among previously inactive populations.